2016
DOI: 10.1177/1352458515621796
|View full text |Cite
|
Sign up to set email alerts
|

RANTES correlates with inflammatory activity and synaptic excitability in multiple sclerosis

Abstract: Background: Alterations of synaptic transmission induced by inflammatory activity have been linked to the pathogenic mechanisms of multiple sclerosis (MS). Regulated upon activation, normal T-cell expressed, and secreted (RANTES) is a pro-inflammatory chemokine involved in MS pathophysiology, potentially able to regulate glutamate release and plasticity in MS brains, with relevant consequences on the clinical manifestations of the disease. Objective: To assess the role of RANTES in the regulation of cortical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…RANTES, now given the immunologic designation CCL5, is one of the principal chemotactic agents that induce recruitment of the immune cells to the CNS via interaction with its corresponding receptor CCR5 51 . RANTES receptors are expressed by hippocampal neurons where it modulates calcium signaling and glutamate release 52 . RANTES has been proposed to be neuroprotective.…”
Section: Resultsmentioning
confidence: 99%
“…RANTES, now given the immunologic designation CCL5, is one of the principal chemotactic agents that induce recruitment of the immune cells to the CNS via interaction with its corresponding receptor CCR5 51 . RANTES receptors are expressed by hippocampal neurons where it modulates calcium signaling and glutamate release 52 . RANTES has been proposed to be neuroprotective.…”
Section: Resultsmentioning
confidence: 99%
“…In the research of E. Sindern et al, CCL5 was not detected in the CSF of RR-MS, but CCL5 release in serum was increased [107]. However, in the 2015 study by Mori F et al, including RRMS patients, CCL5 level was higher in CSF in patients than in the control group, and CCL5 increased during MS disease activity [79]. Other than that, one research by Sørensen et al confirmed the presence of elevated CCL5 in cerebrospinal fluid in patients with acute MS and the fact that lymphocytes expressing CCR5 in the active MS lesions of autopsied brain tissue.…”
Section: Ccl5/ccr5mentioning
confidence: 93%
“…Infiltrating T cells are able to express and secrete chemokine CCL5 [38], but CCL5 is mainly expressed in perivascular cells, vascular endothelial cells and astrocytes [31]. CCL5 is possible to adjust glutamate release and plasticity in the MS brain with associated effects for the disease clinical manifestations [79] and was detected in active demyelinated MS lesions. CCL5 and its receptor CCR5 have strong monocyte chemotaxis [92].…”
Section: Ccl5/ccr5mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Select studies on neuroinflammatory and neurodegenerative disorders report an association between elevated RANTES levels and aberrant inflammatory T cell migration, 36 synaptic excitability, and neuroinflammation. 37 RANTES' association with synaptic excitability may be important to neuronal signaling and may lead to significant downstream consequences. Preclinical models suggest a neuroprotective role for RANTES as well.…”
Section: Discussionmentioning
confidence: 99%